PENGARUH APLIKASI PASTA GIGI DENGAN KANDUNGAN NOVAMIN PADA PERMUKAAN EMAIL GIGI DAN LAMA ETSA TERHADAP KEKUATAN TARIK BRAKET LOGAM: Penelitian Ekperimental Laboratoris - SURYANI, DARMAYANTI DIAN SURYANI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
NovaMin are chemicals in toothpaste produced from the latest technological advances which make up the lining hydroxicarbonate apatite (HCA) when exposed to saliva and has a chemical structure similar to enamel and dentin, and more resistant to acid. This research aims to study the effect of application of toothpaste with NovaMin content on the enamel surface and etching time duration on the tensile strength of the metal bracket. This study was conducted on 60 upper and lower premolars. Applications toothpaste without NovaMin content and contains NovaMin done by brushing toothpaste on circular motion for 2 minutes on each tooth, then immersed in artificial saliva pH 7. Brushing performed once time a day for five days, then do mounting bracket on each tooth according to the etching time groups respectively, ie : 15, 30, and 60 seconds on the sixth day. Twenty-four hours later, the tensile strength measured using Universal Testing Machine. The Statistical analysis used was Two-Lane Anova test . The results showed a tensile strength of the metal bracket on the tooth surface which applied with NovaMin lower than without NovaMin (p <0.05) and the tensile strength of the metal bracket that were etched for 60 seconds higher than etched for 15 and 30 seconds (p < 0, 05). The conclusion of this study is the strength of the metal bracket on the tooth enamel surfaces which applicated with a toothpaste containing NovaMin lower than without NovaMin content, the tensile strength of the metal bracket on the tooth enamel surface which applied without NovaMin and contains NovaMin showed the difference between etching time 15 seconds and 30 seconds, also in etching time 15 seconds and 60 seconds. While etching time 30 seconds showed no difference with 60 seconds. There is no interaction between application totthpaste which contains NovaMin and without NovaMin with etching time 15 seconds, 30 seconds, and 60 seconds. Keywords: NovaMin, etching time, the tensile strength test of orthodontic bracket attachment